2018
DOI: 10.1519/jsc.0000000000001778
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular and Cardiovascular Adaptations in Response to High-Intensity Interval Power Training

Abstract: Romero-Arenas, S, Ruiz, R, Vera-Ibáñez, A, Colomer-Poveda, D, Guadalupe-Grau, A, and Márquez, G. Neuromuscular and cardiovascular adaptations in response to high-intensity interval power training. J Strength Cond Res 32(1): 130-138, 2018-The aim of this study was to determine the efficacy of a high-intensity power training (HIPT) program, and to compare the effects of HIPT to traditional power training (TPT) on the aerobic and power performance. For this purpose, 29 healthy men (23.1 ± 2.7 years) were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…[INSERT FIGURE 1] Table 1 displays the results of the PEDro scale assessment for the longitudinal studies and Table 2 displays the results of the risk of bias assessment for the cross-sectional studies. Of the eight longitudinal studies included, only three studies were deemed to be of fair methodological quality, with five studies deemed to be of poor quality (29,50,(58)(59)(60)(61)(62)(63). The mean PEDro scale score for the longitudinal studies was 3.25 out of 10 suggesting that, on average, the current longitudinal research on HVPT and RPA is of poor methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[INSERT FIGURE 1] Table 1 displays the results of the PEDro scale assessment for the longitudinal studies and Table 2 displays the results of the risk of bias assessment for the cross-sectional studies. Of the eight longitudinal studies included, only three studies were deemed to be of fair methodological quality, with five studies deemed to be of poor quality (29,50,(58)(59)(60)(61)(62)(63). The mean PEDro scale score for the longitudinal studies was 3.25 out of 10 suggesting that, on average, the current longitudinal research on HVPT and RPA is of poor methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…The chronic effect of HVPT training was assessed in five HVPT studies (50,58,60,61,63), with the results of these studies summarised in Table 4. Of the five training studies presented, only one examined the effect of training on RPA (49).…”
Section: [Insert Table 3 Here]mentioning
confidence: 99%
See 2 more Smart Citations
“…This can be understood from research showing both neural and muscle fibre adaptations (i.e. increasing the number of type II fibres) after training with loads that maximise power output [ 12 14 ]. In addition, previous research supporting these findings has suggested that training with maximum power output (Pmax) results in superior improvements in maximal power production compared with other loading conditions [ 5 , 15 ].…”
Section: Introductionmentioning
confidence: 99%